Investigating the Relationship between Social Support and Coping Self-Efficacy with Consideration of Future Consequences during the Quarter-life Crisis - Arubah Malik; Saria Rafiq (Journal of Management Practices, Humanities and Social Sciences, 2022)
The current study aimed to focus on the quarter-life crisis mainly the first phase that required a set of commitments, so it included young adults of Pakistan from 25-35 of age who have at least graduated, had a career, and had a romantic relationship. It was hypothesized that (1) there will be a significant relationship between Consideration of Future Consequences (CFC) and Coping Self-Efficacy (CSE) during the first phase of the quarter-life crisis, and (2) the CFC will impact the relationship between social support and CSE as a moderator variable during the first phase of quarter-life Crisis. Purposive sampling technique was used to collect data from 185 (M = 1.49, SD = 0.501) young adults, including males (51 %) and females (49%). They filled out an online survey that comprised of Multidimensional Scale of Perceived Social Support (MSPSS), Coping Self-Efficacy Scale (CSES), and CFC-14. For the first hypothesis, Pearson Product Correlation was administered, showing a significant moderate positive correlation (p value < 0.01) between CFC and CSF. Moreover, Regression analysis represented (R²=.337, p-value <0.01) that CFC moderates the relationship between social support and CSE. This study will help psychologists, social workers, and educationists who work with young adults and want to enhance their CSE, as it is vital to deal with challenging situations.